Cost of Illness of Diabetic Foot Ulcer in Lower Middle-Income Countries: A Systematic Review - Sinta Wulandari; Alfadea Irbah Allizaputri; Libriansyah; Yunita Nita (Universitas Airlangga, 2026)
Background: Diabetic foot ulcers (DFU) are a consequence of diabetes mellitus (DM) that cause a significant financial burden on the healthcare system, society, and individuals. The average prevalence of DFU was 6.3%. The cost of diabetic foot care is 50% to 200% higher than that of primary diabetes care. Objective: This systematic review aimed to provide an overview of the variations in the economic burden of DFU in lower middle-income countries (LMICs). Methods: This systematic review examined studies published in English that investigated the costs associated with evaluating diabetic foot disease in LMICs. COCHRANE, CINAHL, DOAJ, EMBASE, GOOGLE SCHOLAR, Ovid MEDLINE, PUBMED, SCIENCE DIRECT, and SCOPUS were used as literature sources without publication date restrictions. Results: A systematic search identified six eligible studies conducted across multiple countries. The studies were published between 2000 and 2024, with study durations ranging from 6 to 12 months. These studies showed large variations in cost components, estimating both direct and indirect costs of the disease. The total costs incurred for DFU vary among LMICs, ranging from USD 379.39 to USD 60,014.81 per year. Conclusion: DFU impose a significant economic burden in LMICs, with substantial variations in cost estimates owing to differences in methodology and data availability. Future studies on the cost burden of DFU should be conducted on a larger scale to obtain more accurate cost estimates.